Kebijakan Alokasi Pembagian Dana BOS Sesuai Jumlah Standar Minimal - Tahir K., Muh. (JURNAL ILMIAH GEMA PERENCANA, 2023)
The aim of this paper is to determine whether the allocation of the BOS's distribution of funds meets the minimum standard amount. This study will employ the qualitative research method. Where the researcher will describe the data in the form of sentences. Meanwhile, the researcher is conducting descriptive research. Whereas the descriptive approach only describes the occurrences of phenomena, symptoms, events, and events. The findings of this study, shows that; The BOS Fund is a government program given to education units on the basis of cost reduction or non-personal education to students who cannot afford to relieve other students, as well as implementing compulsory education programs and expanding access to efforts to improve educational quality, because almost all of the cost of activities that have been programmed can take advantage of the BOS budget. The BOS Fund Budget Program aims to reduce the community's burden in financing education in the context of the Quality 9-Year Compulsory Education Program. The BOS Fund Budget Program also plays a role in accelerating the achievement of Minimum Service Standards (SPM) in schools that have not met the SPM, and the achievement of National Education Standards (SNP) in schools that have met the SPM.